Effect of red bean consumption on hemoglobin levels in female adolescents with anemia - Tri Sartika; Helen Evelina Siringo Ringo (Science Midwifery, 2023)
Anemia occurs due to the condition of micronutrient iron (Fe) deficiency which is not only a problem for Indonesia but also experienced by many countries in Asia. The incidence of anemia in Indonesia is still quite high. Based on the 2018 Riskesdas data, the prevalence of anemia in adolescents is 32%, meaning that 3-4 out of 10 adolescents suffer from anemia. This is influenced by nutritional intake habits that are not optimal and lack of physical activity. Red beans have a content that can overcome anemia, namely iron (Fe). The iron content in red beans can help control the amount of hemoglobin in the blood. This study aims to determine the effect of red beans on hemoglobin levels in female adolescents with anemia. Experimental research design with a control group. The sample in this study were female students with Hb levels < 12 gr/dl totaling 56 people consisting of 28 experimental groups and 28 control groups. The results of the study obtained a p value of 0.004 which indicates the effect of red beans on hemoglobin levels in female adolescents. Consumption of red beans which are rich in iron can meet the needs of iron in the body which functions to form hemoglobin and prevent anemia. Suggestion: it is hoped that female adolescents can prevent anemia by consuming red beans.